A comparison of the metabolic response to phagocytosis in human granulocytes and monocytes. - Sagone, A L (1976)
Recent studies indicate that oxygen radicals such as superoxide or singlet oxygen may be important in the functional activity of human granulocytes. We have examined the possible importance of these radicals in the functional capacity of human blood monocytes. Monocytes, like granulocytes, generate chemiluminescence during phagocytosis. Chemiluminescence is impaired 50-90% by superoxide dismutase, an enzyme which enhances the dismutation of superoxide to hydrogen peroxide. These results indicate that superoxide is related to the chemiluminescence generated by monocytes. Superoxide dismutase in a concentration which impaired chemiluminescence also impaired the staphylococcal killing by monocytes. Hexose monophosphate shunt activity and hydrogen peroxide production by granulocytes and monocytes were also evaluated. The oxidation of [1-14C]glucose was used as a measure of hexose monophosphate shunt activity and the oxidation of [14C]formate as an estimation of hydrogen peroxide production. The oxidation of both substrates by monocytes was increased during phagocytosis but, in contrast to results in granulocytes, was not further increased by the addition of superoxide dismutase. These data indicate that superoxide may be important in bactericidal activity of human monocytes. Our results also suggest that the metabolism of oxygen radicals in monocytes and granulocytes may be different.